Graduate employability and graduateness: an overview of concepts, interpretations and emerging issues - Abdul Rahman, Shukran; Shuib, Munir (2011)
This paper discusses the concept of employability by providing its various definitions and explicating graduate employability issues in Malaysia. Instead of contextualising the concept merely to the employment market, this paper attempts to present a framework which also emphasises the needs of society when describing the quality of desirable graduates. This paper then discusses an alternative concept of graduate quality, referred to as graduateness which entails comprehensive attributes of graduates. The paper also discusses a number of initiatives to enhance employability.